Application of Mycorrhizal Technology for Improving Yield Production of Common Bean Plants - Abdel-Fattah, Gamal M.; Shukry, Wafaa M.; Shokr, Mahmoud M.B.; Ahmed, Mai A. (International Journal of Applied Sciences and Biotechnology, 2016)
This study aimed to investigate the effects of arbuscular mycorrhizal (AM) fungi with different levels of NPK fertilizers on yield production of common bean plants which common bean plants were subjected to five levels of NPK fertilizers (0, 25, 50, 75, 100 %). Application of AMF significantly increased the growth and yield components of common beans with minimized the levels of NPK comparing to equivalents non-mycorrhizal ones. The results obtained revealed that inoculation with AMF and the concentrations 50% and 75% of NPK with AMF are the greater than other concentrations and non-mycorrhizal plants. Mycorrhizal Common bean plants had significantly higher number of pods, length of one pod, pods weight, 100 seeds weight, weight of seed/plant and intensity of mycorrhizal colonization(M%) . Concentrations of nutrients (N, P, K, Ca and Mg) and total carbohydrates, crude protein and mycorrhizal dependency of some yield parameters were significantly increased in mycorrhizal plants at different NPK levels when comparing to those of non-mycorrhizal plants paticularly at (50% and 75%) concentration of NPK, but lower Na concentration in mycorrhizal common bean seeds than those of non-mycorrhizal. Int J Appl Sci Biotechnol, Vol 4(2): 191-197